2018
DOI: 10.12659/msm.907288
|View full text |Cite
|
Sign up to set email alerts
|

Dopa-Responsive Dystonia in Han Chinese Patients: One Novel Heterozygous Mutation in GTP Cyclohydrolase 1 (GCH1) and Three Known Mutations in TH

Abstract: BackgroundThis study aimed to clarify the diagnosis and expand the understanding of dopa-responsive dystonia (DRD).Material/MethodsRelevant data from clinical diagnoses and genetic mutational analyses in 3 Han Chinese patients with sporadic DRD were collected and analyzed. Protein structure/function was predicted.ResultsOne novel mutation of c.679A>G (p.T227A) in GCH1 and 3 known mutations of c.457C>T (p.R153X), c.739G>A (p.G247S), and c.698G>A (p.R227H) in tyrosine hydroxylase (TH) have been found and predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…We performed a literature search to clarify whether patients from different geographical regions carrying the R233H mutation and those harboring a heterozygous R233H mutation also displayed similar genotype-phenotype correlations. Therefore, we analyzed reports of 42 eligible patients, which was a sufficient number of cases to support this analysis [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Our analysis revealed that the homozygous R233H mutation frequently manifests as Type A TH deficiency, whereas R233H/nonsense mutation frequently manifests as Type B TH deficiency.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…We performed a literature search to clarify whether patients from different geographical regions carrying the R233H mutation and those harboring a heterozygous R233H mutation also displayed similar genotype-phenotype correlations. Therefore, we analyzed reports of 42 eligible patients, which was a sufficient number of cases to support this analysis [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Our analysis revealed that the homozygous R233H mutation frequently manifests as Type A TH deficiency, whereas R233H/nonsense mutation frequently manifests as Type B TH deficiency.…”
Section: Discussionmentioning
confidence: 96%
“…We analyzed the clinical manifestations, diagnosis, and treatment of the 4 patients diagnosed with TH deficiency at Beijing Tiantan Hospital (Table 1, Ref. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]), . To obtain data on all patients with R233H mutation in TH deficiency reported to date, we searched Medline, PubMed, China National Knowledge Infrastructure (ht tp://www.cnki.net), and Wanfang Data (http://www.wanf angdata.com.cn) databases for papers published in English or Chinese up to August 2020.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations